2022
DOI: 10.5187/jast.2022.e33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various cooling methods and drinking water temperatures on reproductive performance and behavior in heat stressed sows

Abstract: The purpose of this study is to evaluate the effects of multiple cooling systems and different drinking water temperatures (DWT) on the performance of sows and their hair cortisol levels during heat stress. In this study, the effect of four different cooling systems: air conditioner (AC), cooling pad (CP), snout cooling (SC), and mist spray (MS), and two DWT, namely low water temperature (LWT) and high water temperature (HWT) on 48 multiparous sows (Landrace × Yorkshire; 242.84 ± 2.89 kg) was tested. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…According to the findings of our study, an increase in hair cortisol is related to an elevation of room temperature. Fast-growing animals have a substantial reaction to cortisol release under heat stress, due to considerable tissue formation, weight gain, and immunological change [ 21 , 22 ]. Because of the long-term accumulation of cortisol in the hair, earlier studies demonstrated that hair cortisol is a better biomarker of chronic heat stress than blood cortisol [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of our study, an increase in hair cortisol is related to an elevation of room temperature. Fast-growing animals have a substantial reaction to cortisol release under heat stress, due to considerable tissue formation, weight gain, and immunological change [ 21 , 22 ]. Because of the long-term accumulation of cortisol in the hair, earlier studies demonstrated that hair cortisol is a better biomarker of chronic heat stress than blood cortisol [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low ADFI during lactation leads to increased mobilization of body reserves which has been linked to decreased sow's reproductive performance 24 . Increased voluntary feed intake especially in primiparous sows could be significant in maintaining body condition as loss in body condition during lactation may result in reproductive failure 25 . In the present study, lactation feed intake was higher in www.nature.com/scientificreports/ the high dietary fiber diets compared with those fed on lower DF diets.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of animals is considered an essential factor in their growth and welfare, and animals must be exposed to objects that are sufficient to maintain their behavior [27]. It is well known that agonistic behavior during the early post-weaning period, which is common in commercial barren environments, is directly related to poor feed intake and growth in weaning pigs.…”
Section: Behavioral Traitsmentioning
confidence: 99%